Effectiveness of Free Nutritional Meal Program (Mbg) As a Legal Instrument in Protecting Children's Rights in Indonesia - Mumtaza, Cut Wahidah; Malau, Parningotan; Simbolon, Josmangasi; Yulianti, Fanny Aliet (Institut Penelitian dan Pengembangan Mandalika Indonesia, 2025)
The Free Nutritious Meals Program (MBG) is a strategic policy aimed at fulfilling children's right to adequate nutrition as part of the legal protection of human rights. This study analyses the effectiveness of MBG as a legal instrument in guaranteeing children's nutritional rights in Indonesia. This is a normative (doctrinal) legal research employing a statute approach, with limited use of a historical approach to trace the evolution of nutrition-related policies in Indonesia. The analysis focuses on relevant legal instruments, including the 1945 Constitution, Law No. 36 of 2009 on Health, and Presidential Regulation No. 42 of 2020 on Stunting Reduction. The findings reveal that although MBG has a sufficient legal foundation, its effectiveness is hindered by weak monitoring mechanisms, lack of strict sanctions, and low public awareness of their legal rights. Therefore, regulatory strengthening and legal education are essential to enhance the program's effectiveness as an instrument for protecting children's rights.